An Analysis of Students’ Speaking Anxiety in EFL Classroom: A Mixed-Method Study - Khoirzady Taqwa; Didin Nuruddin Hidayat; Zaharil Anasy; Muhammad Syafii S; Adrefiza Adrefiza (Universitas Pahlawan Tuanku Tambusai, 2022)
The study aims to investigate the students’ speaking anxiety levels, find the effect of anxiety, and identify the factors influencing students’ speaking participation. This study involved 62 students in the second semester of the English Education Department, UIN Syarif Hidayatullah Jakarta. This study employed a mixed-method design. To gather the data, a set of questionnaires was utilized based on the Foreign Language Speaking Anxiety Scale by (Horwitz et al., 1986) and an interview. The result of the FLCAS questionnaire classified the category of student anxiety. There were 8 students categorized as very anxious level, 29 students as anxious level, 23 students as mildly anxious level, and 2 students as relaxed level. Students with mildly anxious levels and very anxious levels were interviewed to probe richer data. Further, the study found the effect of students’ speaking anxiety on their speaking participation: considering the idea they want to express, refusing to ask or argue, and being hesitant to participate. This study also found several factors influencing students’ speaking participation, such as English proficiency level, students’ low self-esteem, afraid of making mistakes, lack of preparation, motivation, the method used, and lecturer's attitude